Cathelicidin and Calprotectin Are Disparately Altered in Murine Models of Inflammatory Arthritis and Airway Inflammation - Hemshekhar, Mahadevappa; Piyadasa, Hadeesha; Mostafa, Dina; Chow, Leola N. Y.; Halayko, Andrew J.; Mookherjee, Neeloffer (Frontiers in Immunology, 2020)
Cationic host defence peptides (CHDP) are immunomodulatory molecules that control infections and contribute to immune homeostasis. CHDP such as cathelicidin and calprotectin expression is altered in the arthritic synovium, and in the lungs of asthma and COPD patients. Recent studies suggest a link between airway inflammation and the immunopathology of arthritis. Therefore, in this study we compared the abundance of mouse cathelicidin (CRAMP), defensins, and calprotectin subunits (S100A8 and S100A9) in murine models of collagen-induced arthritis (CIA) and allergen house dust mite (HDM)-challenged airway inflammation. CRAMP, S100A8 and S100A9 abundance were significantly elevated in the joint tissues of CIA mice, whereas these were decreased in the lung tissues of HDM-challenged mice, compared to naïve. We further compared the effects of administration of two different synthetic immunomodulatory peptides, IG-19 and IDR-1002, on cathelicidin and calprotectin abundance in the two models. Administration of IG-19, which controls disease progression and inflammation in CIA mice, significantly decreased CRAMP, S100A8 and S100A9 levels to baseline in the joints of the CIA mice, which correlated with the decrease in cellular influx in the joints. However, administration of IDR-1002, which suppresses HDM-induced airway inflammation, did not prevent the decrease in the levels of cathelicidin and calprotectin in the lungs of HDM-challenged mice. Cathelicidin and calprotectin levels did not correlate with leukocyte accumulation in the lungs of the HDM-challenged mice. Results of this study suggest that endogenous cathelicidin and calprotectin abundance are disparately altered, and may be differentially regulated, within local tissues in airway inflammation compared to arthritis.